Accuracy of intraoral real-time navigation versus static, CAD/CAM-manufactured pilot drilling guides in dental implant surgery: an in vitro study - Robert Stünkel; Alexander-Nicolai Zeller; Thomas Bohne; Florian Böhrnsen; Edris Wedi; David Raschke; Philipp Kauffmann (figshare, 2022)
Abstract Background Nowadays, 3D planning and static for dynamic aids play an increasing role in oral rehabilitation of the masticatory apparatus with dental implants. The aim of this study is to compare the accuracy of implant placement using a 3D-printed drilling guide and an intraoral real-time dynamic navigation system. Methods A total of 60 implants were placed on 12 partially edentulous lower jaw models. 30 were placed with pilot drilling guides, the other half with dynamic navigation (DENACAM®). In addition, implant placement in interdental gaps and free-end situations were investigated. Accuracy was assessed by cone-beam computed tomography (CBCT). Results Both systems achieved clinically acceptable results, yet more accurate results regarding the offset of implant base and tip in several spatial dimensions were achieved using drilling guides (each p < 0.05). With regard to angulation, real-time navigation was more precise (p = 0.0016). Its inaccuracy was 3°; the template-guided systems was 4.6°. Median horizontal deviation was 0.52 mm at base and 0.75 mm at tip using DENACAM®. When using the pilot drill guide, horizontal deviation was 0.34 mm in the median and at the tip by 0.59 mm. Regarding angulation, it was found that the closer the drill hole was to the system's marker, the better navigation performed. The template did not show this trend (p = 0.0043; and p = 0.0022). Conclusion Considering the limitations of an in vitro study, dynamic navigation can be used be a tool for reliable and accurate implantation. However, further clinical studies need to follow in order to provide an evidence-based recommendation for use in vivo.
Keywords: Space Science; Medicine; Sociology; 69999 Biological Sciences not elsewhere classified; 80699 Information Systems not elsewhere classified; Cancer